The synthesis and application of heparin-based smart drug carrier. (20th April 2016) - Li, Qingxuan; Gan, Lu; Tao, Hong; Wang, Qian; Ye, Lin; Zhang, Aiying; Feng, Zengguo
Graphical abstract: Highlights: Heparin as a versatile biocompatible platform for smart DDS construction. pH sensitive release of both PTX and DOX as well as tumor targeting ability. Binary drug (PTX and DOX) loading ability in one carrier. High PTC loading efficiency of heparin based polymer drug. The loading of DOX and folic acid via electrostatic interaction. Abstract: Heparin based polymer drug which could self-assemble into sphere micelle in water was firstly prepared by grafting paclitaxel (PTX) into the hydroxyl of heparin via aconitic bond as pH sensitive spacer. Positive charged drug DOX·HCl and cationic folic acid (CFA) can be further loaded into the polymer drug via electrostatic interaction in aqueous solution so as to prepare smart drug carrier. The drug carrier was able to release more PTX and DOX at pH 4.8 than that at pH 7.4, exhibiting pH sensitivity for two drugs. Furthermore, tumor cell cytotoxicity test proved it possessed significant cytotoxicity against tumor cells MDA-MB-231 as well as its active tumor targeting ability resulting from the loading of CFA. Cellular uptake and intracellular distribution were further revealed by confocal laser scanning microscopy (CLSM). In conclusion, this paper not only provided a simple strategy but also indicated heparin is a versatile platform for the design of smart drug carrier. The as-prepared drug carrier also showed promising potential in chemotherapy.